Hemoglobin S and C affect protein export in Plasmodium falciparum-infected erythrocytes - Kilian, Nicole; Srismith, Sirikamol; Dittmer, Martin; Ouermi, Djeneba; Bisseye, Cyrille; Simpore, Jacques; Cyrklaff, Marek; Sanchez, Cecilia P.; Lanzer, Michael (Biology open, 2015)
Malaria is a potentially deadly disease. However, not every infected person develops severe symptoms. Some people are protected by naturally occurring mechanisms that frequently involve inheritable modifications in their hemoglobin. The best studied protective hemoglobins are the sickle cell hemoglobin (HbS) and hemoglobin C (HbC) which both result from a single amino acid substitution in β-globin: glutamic acid at position 6 is replaced by valine or lysine, respectively. How these hemoglobinopathies protect from severe malaria is only partly understood. Models currently proposed in the literature include reduced disease-mediating cytoadherence of parasitized hemoglobinopathic erythrocytes, impaired intraerythrocytic development of the parasite, dampened inflammatory responses, or a combination thereof. Using a conditional protein export system and tightly synchronized Plasmodium falciparum cultures, we now show that export of parasite-encoded proteins across the parasitophorous vacuolar membrane is delayed, slower, and reduced in amount in hemoglobinopathic erythrocytes as compared to parasitized wild type red blood cells. Impaired protein export affects proteins targeted to the host cell cytoplasm, Maurer's clefts, and the host cell plasma membrane. Impaired protein export into the host cell compartment provides a mechanistic explanation for the reduced cytoadherence phenotype associated with parasitized hemoglobinopathic erythrocytes.
Im Titel erscheint der Name "Plasmodium falciparum" schräggestellt
Gesehen am 01.07.2020